Nephroprotective effect of Berberis baluchistanica against gentamicin-induced nephrotoxicity in rabbit - Samreen Pervez; Muhammad Saeed; Haroon Khan; Muhammad Shahid; Irfan Ullah (Bangladesh Pharmacological Society, 2018)
The present study was conducted to explore the protective effect of B. baluchistanica against gentamicin-induced renal toxicity in rabbits. Phytochemical investigations lead to the isolation of berberine and palmatine. The crude hydro-methanolic extract at various doses (100, 200 and 300 mg/kg body weight) elicited strong nephroprotective effects by restoring various biomarkers which were deranged by gentamicin  such as creatinine, urea, serum uric acid levels (p<0.001) in plasma and urine output creatinine clearance, urinary protein and γ-glutamyl transferase level (p<0.001) in urine in a dose dependent manner. The mediators involved in oxidative stress such malondialdehyde, reduced glutathione, glutathione peroxidase, and catalase levels were significantly (P˂0.05-0.001) modulated in kidney tissue homogenate. Correspondingly, there is a significant (P<0.05) recovery in kidney weight and % loss in body weight compare to GM group. From these results, it is possible that B. baluchistanica exhibited protective effect mediated through the presence of berberine  and palmatine. Video Clip of Methodology: Histopathology:   7 min 24 sec   Full Screen   Alternate